2009
DOI: 10.1158/1535-7163.mct-08-0636
|View full text |Cite
|
Sign up to set email alerts
|

Genomics screen in transformed stem cells reveals RNASEH2A, PPAP2C, and ADARB1 as putative anticancer drug targets

Abstract: Since the sequencing of the human genome, recent efforts in cancer drug target discovery have focused more on the identification of novel functions of known genes and the development of more appropriate tumor models. In the present study, we investigated in vitro transformed human adult mesenchymal stem cells (MSC) to identify novel candidate cancer drug targets by analyzing the transcriptional profile of known enzymes compared with non-transformed MSC. The identified enzymes were compared with published cance… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
61
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 43 publications
7
61
0
Order By: Relevance
“…Of note, we detected the heterogeneous RNase H2 subunit's mRNA expression in colon cancer tissues: while RNASEH2C was suppressed, RNASEH2A was upregulated. Such a finding is in agreement with the findings of Flanagan et al [34] , which showed RNASEH2A upregulation in breast/bladder/brain/head and neck cancers, in seminomas, and in leukemia and which further suggested a pro-survival role of RNASEH2A in cancers. Although RNASEH2A encodes the main catalytic subunit of RNase H2, which cleaves misincorporated ribonucleotide during DNA replication [6,35] , RNASEH2B and RNASEH2C could form a stable complex without RNASEH2A , and they could interact with other proteins to exert cellular functions beyond enzymatic activity [36,37] .…”
Section: Tcga-aa-3511supporting
confidence: 93%
“…Of note, we detected the heterogeneous RNase H2 subunit's mRNA expression in colon cancer tissues: while RNASEH2C was suppressed, RNASEH2A was upregulated. Such a finding is in agreement with the findings of Flanagan et al [34] , which showed RNASEH2A upregulation in breast/bladder/brain/head and neck cancers, in seminomas, and in leukemia and which further suggested a pro-survival role of RNASEH2A in cancers. Although RNASEH2A encodes the main catalytic subunit of RNase H2, which cleaves misincorporated ribonucleotide during DNA replication [6,35] , RNASEH2B and RNASEH2C could form a stable complex without RNASEH2A , and they could interact with other proteins to exert cellular functions beyond enzymatic activity [36,37] .…”
Section: Tcga-aa-3511supporting
confidence: 93%
“…This highlights the need to further investigate the molecular mechanisms that contribute to resistance. Transcriptional profiles have previously helped identify druggable pathways in cancer (78)(79)(80)(81), and recent sequencing efforts have identified mutated molecular pathways involved in ETR in breast cancer (77). However, epigenetic reprogramming of regulatory elements is increasingly being recognized for its contribution to cancer development (82).…”
Section: Discussionmentioning
confidence: 99%
“…These investigators also compared data from a genomic screen between normal and transformed mesenchymal stem cells. PPAP2C / LPP2 was identifi ed as one target whose expression is elevated in numerous carcinomas and sarcomas ( 100 ). In contrast to the targeting of LPP1 and LPP2, knockdown of LPP3 (Ppap2C) in mice produces a very severe phenotype resulting in embryo death around E9.5 ( 101 ).…”
Section: Noncatalytic Actions Of Lppsmentioning
confidence: 99%